EVALUASI KINERJA POLA OPERASI WADUK (POW) WONOGIRI 2014 - Dinia Anggraheni; Rachmad Jayadi; Istiarto Istiarto (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2017)
Wonogiri Reservoir is one of the reservoirs in Central Java which is a multifunctional reservoir. The reservoir serves many functions as flood control, irrigation and raw water supply, and hydropower (PLTA). For managing the fulfillment of these functions, Wonogiri Reservoir has a Reservoir Operating Rule to adjust the elevation and release discharge every mid-month. However, There was for the condition of Wonogiri Reservoir in October 2014. The water level of October 30, 2014, was at+126,66 m, while in Reservoir Operating Rule, the water level was supposed to be at +127,63 m. Therefore, the operating rule performance needs to evaluate, especially in 2014. The evaluation step began by conducting a water balance study with the demand for irrigation water and raw water, actual release, and inflow into the reservoir. The next step was optimizing the operating rule of the reservoir by the objective function of maximizing the comparison between release and demand for the fulfillment of irrigation water with 10 years data. The final step was evaluating the Wonogiri Reservoir Operating Rule in 2014 using a new operating rule generated from the optimization process. Based on the results of the study can be concluded that the inflow that occurred in 2014 can fulfill the needs of irrigation water and maintain elevation in accordance with the operating rule in 2014.